IN VITRO CHEMO-PREVENTATIVE ACTIVITY OF STRELITZIA NICOLAI ARIL EXTRACT CONTAINING BILIRUBIN - Dwarka, Depika; Thaver, Veneesha; Naidu, Mickey; Koorbanally, Neil A.; Baijnath, Himansu (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: The discovery of the only animal pigment, bilirubin, in the plant Strelitzia nicolai has triggered a vast number of questions regarding bilirubin’s formation and its role in the human body. Recent studies have confirmed that bilirubin at certain levels have many medical benefits. Various case studies have revealed that bilirubin is a potent antioxidant. Cervical cancer is one of South Africa’s largest womens’ health crises. It is estimated that it affects one out of 41 South African women and kills approximately 8 women in the country every day. Thus, the aim of this study was to investigate if the aril extract of Strelitzia nicolai (Regel and Körn.) containing bilirubin possesses anti-cancer activity and to determine its effect on the induction of apoptosis. Materials and methods: The DPPH activity was firstly used to determine the antioxidant effect of the extract. Thereafter, the cytotoxic effect was tested using the XTT assay. Apoptosis was confirmed and quantified using the Annexin V-PE kit and the morphology was studied using acridine orange and ethidium bromide. Results: The aril extract decreased cell viability by 52% and induced apoptosis in HeLa cells; as shown by the Annexin V-PE Apoptosis detection kit and morphological studies with acridine orange/ethidium bromide staining. Conclusion: The activity of the extract as a potent antioxidant was immensely enhanced as compared to the bilirubin standard. These results suggest that S. nicolai aril extract containing bilirubin works synergistically as opposed to bilirubin on its own. Furthermore, this extract might be a good candidate for the therapeutic intervention of cervical cancer.